Social Media and Health Policy - Charalambous Andreas (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2022)
The current era is characterized by the vibrant and rapidly evolving communication technologies. Communication in any form has evolved and now includes media such as Facebook, Twitter, and Instagram to report a few. Communicating and consuming information has shifted from the more traditional ways to new ones as part of this communication evolution. Cancer is an area of healthcare where such social media have been championed either to promote public awareness and drive campaigns or influence political decision-making. Although health-care lags behind many other industries in adopting social media as a part of a business or policy strategy, the increasing engagement of patients, the public, and the policymakers in social media raised the need for integrating these tools as a part of an overall program to support the strategic imperatives of the health care. As these and other new ways to communicate are introduced to the world and injected into our cultural and political systems, the question that raises here is: "How successful are social media in influencing health policy?"